Periodontal Status, Tooth Loss and Self-Reported Periodontal Problems Effects on Oral Impacts on Daily Performances, OIDP, in Pregnant Women in Uganda: A Cross-Sectional Study - Wandera, Margaret N.; Engebretsen, Ingunn M.; Rwenyonyi, Charles M.; Tumwine, James; Åstrøm, Anne N. (Health and quality of life outcomes, 2009)
An important aim of antenatal care is to improve maternal health- and well being of which oral health is an important part. This study aimed to estimate the prevalence of oral impacts on daily performances (OIDP) during pregnancy, using a locally adapted OIDP inventory, and to document how periodontal status, tooth-loss and reported periodontal problems are related to oral impacts.Pregnant women at about 7 months gestational age who were members of a community based multi-center cluster randomized community trial: PROMISE EBF: Safety and Efficacy of Exclusive Breast feeding in the Era of HIV in Sub-Saharan Africa, were recruited in the district of Mbale, Eastern Uganda between January 2006 and June 2008. A total of 877 women (participation rate 877/886, 98%, mean age 25.6, sd 6.4) completed an interview and 713 (participation rate 713/886, 80.6%, mean age 25.5 sd 6.6) were examined clinically with respect to tooth-loss and according to the Community Periodontal Index, CPI.Seven of the original 8 OIDP items were translated into the local language. Cronbach's alpha was 0.85 and 0.80 in urban and rural areas, respectively. The prevalence of oral impacts was 25% in the urban and 30% in the rural area. Corresponding estimates for CPI>0 were 63% and 68%. Adjusted ORs for having any oral impact were 1.1 (95% CI 0.7-1.7), 1.9 (95% CI 1.2-3.1), 1.7 (1.1-2.7) and 2.0 (0.9-4.4) if having respectively, CPI>0, at least one tooth lost, tooth loss in molars and tooth loss in molar-and anterior regions. The Adjusted ORs for any oral impact if reporting periodontal problems ranged from 2.7(95% CI 1.8-4.2) (bad breath) through 8.6(95% CI 5.6-12.9) (chewing problem) to 22.3 (95% CI 13.3-35.9) (toothache).A substantial proportion of pregnant women experienced oral impacts. The OIDP impacts were most and least substantial regarding functional- and social concerns, respectively. The OIDP varied systematically with tooth loss in the molar region, reported chewing-and periodontal problems. Pregnant women's oral health should be addressed through antenatal care programs in societies with limited access to regular dental care facilities.
Keywords: Oral Health; Periodontal Disease; Tooth Loss; Oral Health Care; Molar Region